The impact of therapy on the quality of life in asymptomatic patients with freshly detected hypertension - Mishra, Satish Chandra; Singh, Vishal; Prakash, Sudeep; Pandey, Pushkar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Hypertension is an commonly encountered disease which adversely affect all aspects of quality of life (QoL). The existing studies are confounded by the presence of multiple comorbidities and inclusion of elderly, which by themselves impairs the QoL. There is thus a need to study the impact of hypertension on QoL, in isolation. Method: This is a single center, prospective, intention to treat, observation study. The aim of the study is to evaluate the change in the QoL over six months, in newly diagnosed asymptomatic patients of hypertension. The tools used to assess the QoL included World Health Organisation’s Quality of Life Questionnaire (WHOQOL- BREF) and Short Form-36 (SF-36). Result: A total of 232 patients (172 males and 60 females) were enrolled in the study. The mean age was 44.66 years. A total of 102 patients (43.97%) had stage-1 and 130 patients (56.03%) had stage-2 hypertension. The female gender is associated with a higher likelihood of presentation with stage-2 hypertension. The male cohort had a better baseline QoL. The desired blood pressures was achieved in 40.52%. With therapy, the QoL improved significantly; sub-hoc analysis showed, the improvement was higher in males and those with stage-1 hypertension. There is an inverse relationship between the QoL and requirement for higher number of antihypertensive mediations. Conclusions: In patients with asymptomatic primary hypertension, treatment improves all aspects of QoL. The factors adversely affecting the QoL include female gender, higher stage of hypertension, poor blood pressure control and requirement of higher numbers of antihypertensive medicine.